Effectiveness of Nylon Membrane in Improving the Quality of Hospital Wastewater Based on COD and Ammonia Parameters - Eka Yulia Salsabiilah; Nindha Ayu Berlianti Nindha; Wenny Maulina (Universitas Pendidikan Ganesha, 2026)
Hospital wastewater generally contains high levels of organic compounds and nitrogen, with COD and ammonia values exceeding environmental quality standards. Conventional treatment methods are often suboptimal, requiring efficient and stable alternative technologies. This study aims to analyze and evaluate the effects of variations in nylon mass fraction on the performance of ultrafiltration membranes, including swelling degree, flux, and rejection capacity for reducing COD and ammonia. This study is a laboratory experiment using a membrane mass-fraction variation design. The study included five types of nylon membranes (A–E) that were tested using hospital wastewater samples. The membranes were synthesized by the phase inversion method, and performance testing was conducted via ultrafiltration, swelling measurements, permeate flux, and analyses of COD and ammonia. Data were analyzed descriptively and quantitatively using rejection coefficients and operational stability values. The results showed that increasing the nylon mass fraction decreased the degree of swelling and flux, but increased rejection up to optimum conditions. Membrane D showed the best performance in reducing COD and ammonia and had better stability. These findings indicate that optimizing the nylon mass fraction could improve the effectiveness of membrane-based treatment of hospital wastewater.